Multiphase Structure and Electromechanical Behaviors of Aliphatic Polyurethane Elastomers - Xiang, Dong; He, Jingjing; Cui, Tongtong; Liu, Li; Shi, Qi Song; Ma, Lan Chao; Liang, Yongri (Macromolecules, 2018)
Understanding the relationship between multiphase structure and electromechanical property of thermoplastic dielectric elastomers is significantly important in the developments of high-performance and novel dielectric elastomers. In this work, we fabricated a series of aliphatic polyurethane elastomers (PUEs) based on hydroxyl-terminated butadiene-acrylonitrile copolymer (HTBN), hexamethylene diisocyanate (HDI), and various lengths of linear aliphatic diols and investigated effect of their microstructure and morphology on dielectric and electromechanical properties. The FTIR, WAXS, SAXS, and viscoelastic AFM results showed that the PUEs existed in crystalline phase, hard domain (HD) and soft domain (SD) phases composed HD-rich region and few HDs and SD composted SD-rich region by crystallization and microphase separation. Also, the crystal morphology and crystallinity of PUEs are strongly influenced by the length of chain extender due to the chain extender adopting various conformations by hydrogen bonding. The mechanical and electric fields induced responses of segment motions in PUEs at below room temperature were relative to the constrained SS motions from HD-rich and SD-rich regions. The electric field induced strain of PUEs was actuated by both Maxwell stress and electrostriction effect, of which contribution of electrostriction effect was above 64% in total actuation strain. In addition, we found that the effect of electrostriction on the actuation strain played an important role in improving the actuation strain of PUEs at lower electric field. Our results showed that the dielectric and electromechanical properties of PUEs can be adjusted by controlling the crystallization and microphase separation.